1998
DOI: 10.1063/1.475908
|View full text |Cite|
|
Sign up to set email alerts
|

In situ studies of thiol self-assembly on gold from solution using atomic force microscopy

Abstract: The kinetics and mechanism for the solution-phase adsorption of n-alkanethiols onto gold to form self-assembled monolayers (SAMs) have been monitored in situ using atomic force microscopy (AFM). Time-dependent AFM images reveal detailed structural information about the adsorbed layer during its growth. In 2-butanol, CH3(CH2)17SH molecules initially adsorb on gold with the molecular axis of their hydrocarbon chains oriented parallel to the surface. As the surface coverage increases to near saturation, a two-dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
155
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(177 citation statements)
references
References 54 publications
20
155
2
Order By: Relevance
“…The results have revealed that the speed of EG 6 (longer chain thiols compared to EG 3 ) diffusion to form SAMs on gold surfaces under PDMS is slower than that of EG 3 . These results are different from that of thiols to form SAMs on the interface between gold and gas, in which longer chain length thiols covered the gold surface more rapidly than shorter chain length thiols [24]. In Fig.…”
Section: Resultsmentioning
confidence: 43%
“…The results have revealed that the speed of EG 6 (longer chain thiols compared to EG 3 ) diffusion to form SAMs on gold surfaces under PDMS is slower than that of EG 3 . These results are different from that of thiols to form SAMs on the interface between gold and gas, in which longer chain length thiols covered the gold surface more rapidly than shorter chain length thiols [24]. In Fig.…”
Section: Resultsmentioning
confidence: 43%
“…As discussed above, the coordinate bond could actually form between the -SH group and gold surface in the initial stage, followed by the dissociation of S-H bond that results in a thiyl radical, which would finally form a gold-thiolate covalent bond at the gold-sulfur interface [45][46][47][48][49][50][51][54][55][56][57][58] . These findings indicate that the formation of Au-S covalent bonds needs a certain time to complete.…”
Section: Resultsmentioning
confidence: 99%
“…The formation of a Au-S covalent bond is a complicated process, involving the dissociation of the S-H bond and followed by the formation of the Au-S covalent bond [45][46][47][48][49][50][51] . The dissociated hydrogen atoms could either adsorb on gold surfaces or release from the surface in the form of H 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their simplicity, highly ordered structures, and chemical stability make these systems ideal for study with a variety of techniques including atomic force microscopy, 5,6 infrared spectroscopy, 7,8 high-resolution electron-energy-loss spectroscopy, 9 grazing X-ray diffraction, 10 scanning tunneling microscopy (STM), 11-17 scanning probe microscopy, 18 lowenergy electron diffraction (LEED), [19][20][21] He atom diffraction, 22,23 and theory. 25-31 Despite 1…”
Section: Introductionmentioning
confidence: 99%